The collapsing empire [large type] - Scalzi, John, 1969- (Scalzi, John, 1969- Interdependency, 2017)
Riding an extradimensional field called the Flow, humanity spreads to innumerable other worlds. When it's discovered that the Flow is moving, possibly separating all human worlds forever, three individuals must race against time to discover what can be salvaged from an interstellar empire on the brink of collapse.